THE CONTENT VALIDITY OF SUMMATIVE TEST FOR THE TENTH GRADE STUDENTS - Syahfitri Isabella Simatupang; Meisuri Meisuri; Nora Ronita Dewi (Universitas Negeri Medan, 2019)
This study was a descriptive qualitative research. It aimed to describe the content validity of the English summative test items for the tenth grade students at SMK Imelda Medan. This study used documentary analysis in collecting the data. The data of this research were the English summative test items for the odd semester of the tenth grade students made by the English teacher at SMK Imelda Medan in academic year of 2018/2019. The English summative items were classified into five categorizations: interpersonal conversation, transactional conversation, short functional texts, genre, and grammar. Based on the analysis of data, 22 out of 30 English summative test items for the tenth grade students were suitable to the syllabus (73%) with the most dominant topic about transactional conversation (10 items while there were 10 out of 30 items were irrelevant (27%) to the syllabus because the items discuss about the topics that are not irrelevant to the syllabus. Keywords: Summative Test, Content Validity, and Syllabus